Distúrbios do olfato e paladar após a fase aguda da COVID-19: um estudo observacional sobre o impacto neuropsiquiátrico - Ferrão, Ana Clara Miotello (2023)
Introduction: The influence of the chemosensory disorders on quality of life has been studied since before the pandemic, since other viral infections have olfactory and gustatory disfunctions. However, the persistence of these disorders and the relation with neuropsychiatric symptoms during and after the COVID-19 pandemic has highlighted the need for studies on the impact on the mental health of the affected individuals. Objective: To estimate the frequency of chemosensory impairment after the acute phase of COVID-19 and its relationship with the development of neuropsychiatric disorders. Methods: This is a cross-sectional descriptive study based on primary data collected through a questionnaire made available on the Survey Monkey online platform between May and July 2023. The questionnaire was based on questions about sociodemographic information, acute infection data, olfactory disorder data, assessment and memory assessment. They were eligible for the study, individuals living in the state of Mato Grosso do Sul, aged over 18 years and with a previous diagnosis of COVID-19. Results: The study included 495 participants who met the eligibility criteria. The majority was residents of Campo Grande (82,7%), aged up to 39 years (44,9%) and female (70.9 %). Regarding the prevalence of chemosensory disorders, 62,4% had a decline in smell, 61% had a decline in taste and 13.3% had parosmia. Regarding the association between olfactory loss and the occurrence of neuropsychiatric symptoms, there was a greater occurrence symptoms in individuals with olfactory loss (regardless of the time of the disorder) in 7 of the 9 aspects surveyed: feeling sad or depressed, feeling impatient with people around them, inability to enjoy things as before, feeling hopelessness about the future, feelings anxious or nervous, feeling muscle tension and experience intense anxiety leading to panic. The same association with olfactory disorder was observed when were questioned about self-perceived memory problems. Conclusion: Chemosensory are a highly relevant factor in Covid-19 since they have a high prevalence and are related to a negative impact on individual’s quality of life. In addition, it is suggested that loss of smell and taste is related to greater occurence of neuropsychiatric disorders and memory deficits.